Distinctive Structure and Assembly of Phyllosphere Microbial Communities between Wild and Cultivated Rice - Yin, Yue; Wang, Yi-Fei; Cui, Hui-Ling; Zhou, Rui; Li, Lv; Duan, Gui-Lan; Zhu, Yong-Guan (Microbiology spectrum, 2023)
Plant microbiota are being considered a lever to increase the sustainability of food production under a changing climate. In particular, the microbiomes associated with ancestors of modern cultivars have the potential to support their domesticated cultivars. Wild rice has been demonstrated to possess enriched genetic diversity and multiple valuable traits involved in disease/pest resistance and abiotic stress tolerance, which provides a potential resource for sustainable agriculture. However, unlike the plant compartments such as rhizosphere, the structure and assembly of phyllosphere microbial communities of wild rice remain largely unexplored. Through amplicon sequencing, this study compared the phyllosphere bacterial and fungal communities of wild rice and its neighboring cultivated rice. The core phyllosphere microbial taxa of both wild and cultivated rice are dominated with Pantoea , Methylobacterium , Nigrospora , and Papiliotrema , which are potentially beneficial to rice growth and health. Compared to the cultivated rice, Methylobacterium , Sphingomonas , Phaeosphaeria , and Khuskia were significantly enriched in the wild rice phyllosphere. The potentially nitrogen-fixing Methylobacterium is the dominated wild-enriched microbe; Sphingomonas is the hub taxon of wild rice networks. In addition, the microbiota of wild rice was more governed by deterministic assembly with a more complicated and stable community network than the cultivated rice. Our study provides a list of the beneficial microbes in the wild rice phyllosphere and reveals the microbial divergence between wild rice and cultivated rice in the original habitats, which highlights the potential selective role of wild rice in recruiting specific microbiomes for enhancing crop performance and promoting sustainable food production. IMPORTANCE Plant microbiota are being considered a lever to increase the sustainability of food production under a changing climate. In particular, the microbiomes associated with ancestors of modern cultivars have the potential to support their domesticated cultivars. However, few efforts have been devoted to studying the biodiversity and functions of microbial communities in the native habitats of ancestors of modern crop species. This study provides a list of the beneficial microbes in the wild rice phyllosphere and explores the microbial interaction patterns and the functional profiles of wild rice. This information could be useful for the future utilization of the plant microbiome to enhance crop performance and sustainability, especially in the framework of sustainable agroecosystems.